Molecular epidemiology of Coxsackievirus A16 strains isolated from children in Yamagata, Japan between 1988 and 2011. (14th May 2013) - Mizuta, Katsumi; Abiko, Chieko; Aoki, Yoko; Ikeda, Tatsuya; Matsuzaki, Yoko; Hongo, Seiji; Itagaki, Tsutomu; Katsushima, Noriko; Ohmi, Akira; Nishimura, Hidekazu; Ahiko, Tadayuki
ABSTRACT To clarify the longitudinal molecular epidemiology of coxsackievirus A16, phylogenetic analysis based on the VP1 region of 220 isolates in Yamagata, Japan was performed. The resultant phylogenetic tree indicates that the Yamagata isolates and reference strains can be readily genotyped into three genogroups, and 0, 12 and 208 isolates belonged to the first, second, and third genogroups, respectively. The first genogroup includes only the prototype strain, the second strains that had disappeared by the end of the 20th century and the third comprises those that have been circulating since then in local communities, such as Yamagata.